2022
DOI: 10.1002/anie.202211948
|View full text |Cite
|
Sign up to set email alerts
|

The Continuum Between Hexagonal Planar and Trigonal Planar Geometries**

Abstract: New heterometallic hydride complexes that involve the addition of {Mg−H} and {Zn−H} bonds to group 10 transition metals (Pd, Pt) are reported. The side‐on coordination of a single {Mg−H} to Pd forms a well‐defined σ‐complex. In contrast, addition of three {Mg−H} or {Zn−H} bonds to Pd or Pt results in the formation of planar complexes with subtly different geometries. We compare their structures through experiment (X‐ray diffraction, neutron diffraction, multinuclear NMR), computational methods (DFT, QTAIM, NCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…of 2 from 1 is calculated to form Int‐1 with a small energy cost (Δ G ° 298K =10.3 kcal mol −1 ). This process occurs with a shift in the bonding of 1 along the continuum from hexagonal planar toward trigonal planar, [35] strengthening the Mg‐H interactions in the equatorial plane, and pre‐organising the complex for dissociation of an equivalent of 2 . Similar coordinatively unsaturated intermediates were recently described in related systems for the zincation of C−H bonds [24] .…”
Section: Methodsmentioning
confidence: 99%
“…of 2 from 1 is calculated to form Int‐1 with a small energy cost (Δ G ° 298K =10.3 kcal mol −1 ). This process occurs with a shift in the bonding of 1 along the continuum from hexagonal planar toward trigonal planar, [35] strengthening the Mg‐H interactions in the equatorial plane, and pre‐organising the complex for dissociation of an equivalent of 2 . Similar coordinatively unsaturated intermediates were recently described in related systems for the zincation of C−H bonds [24] .…”
Section: Methodsmentioning
confidence: 99%
“…of 2 from 1 is calculated to form Int‐1 with a small energy cost (Δ G ° 298K =10.3 kcal mol −1 ). This process occurs with a shift in the bonding of 1 along the continuum from hexagonal planar toward trigonal planar, [35] strengthening the Mg‐H interactions in the equatorial plane, and pre‐organising the complex for dissociation of an equivalent of 2 . Similar coordinatively unsaturated intermediates were recently described in related systems for the zincation of C−H bonds [24] .…”
Section: Methodsmentioning
confidence: 99%
“…Shortly thereafter, the Crimmin group expanded on their study of the gap between the hexagonal planar MH Mg{ Ar nacnac}). 425 X-ray and neutron diffraction studies in combination with computational studies revealed that the zincbased donors tend to form C 3h geometries, while the magnesium analogues prefer to adopt a D 3h symmetry (Scheme 84b). The evidence from this work indicates that the hexagonal planar bonding extreme is favored in systems with large ionic contributions to the M−Mg interaction, implying a formal description of the system as a metalate(0) fragment [MH 3 ] 481 This compound formed by formal Cp − transfer with release of a phosphine ligand from 715, as observed upon reaction with either MgCp 2 or TlCp.…”
Section: Transition-metal Magnesium Compounds and Related Heavier Alk...mentioning
confidence: 99%
“…Ion-pairing interactions can occur in the absence of a cation sequestering agent. While studies by Fürstner, Hevia, Mountford, ,,, Crimmin, Wolf, Peters, , and Lu, , among other contributions, illustrate that ion-pairing is a frequent phenomenon, only a handful of the investigations explicitly address the influence of such interactions on their reactivity. However, from these investigations it has become clear that the countercation may have profound influence on the reaction patterns, stoichiometric or catalytic, of metalates.…”
Section: Synthesis and Basic Reactivity Patterns Of D-block Metalatesmentioning
confidence: 99%